EMOTIONAL INTELLIGENCE AND PEDAGOGICAL COMPETENCE ON THE PERFORMANCE OF MUHAMMADIYAH PAREPARE JUNIOR HIGH SCHOOL TEACHERS - Adisaputra, Whisnu (Journal of Entrepreneur, Business and Management, 2024)
This study aims to investigate, scrutinize, and elucidate the effects of Emotional Intelligence and Pedagogical Competence on the performance of teachers at Muhammadiyah Parepare Junior High School. The research employs a quantitative descriptive approach, involving a population and sample of 33 teachers. Data gathering encompasses interviews, surveys, and a review of existing literature. The collected data will undergo analysis using statistical tools and SPSS software version 24. The findings of the study reveal that: 1. Emotional Intelligence exerts a positive and noteworthy influence on the performance of teachers at Muhammadiyah Parepare Junior High School. In general, Emotional Intelligence plays a pivotal role in enhancing teacher performance, a critical factor in attaining organizational objectives. 2. Pedagogical Competence similarly demonstrates a positive and significant impact on the performance of teachers in Muhammadiyah Parepare Junior High School. This competence is a vital element that assists teachers in optimizing their potential to contribute to organizational goals with a heightened sense of awareness.